(untitled) (International Journal of Business, Economics and Management, 2019)
In this research, we study factors such as consumer attitudes and personal innovativeness in order to understand the effect of loyalty on satisfaction with mobile wallet applications in Thailand. We developed a research model, based upon previous research, where we propose and examine four constructs. In general, consumer attitudes and personal innovativeness loaded strongly on both loyalty and satisfaction with the Thai consumers sampled. We found strong support for all of the hypothesized relationships, albeit some at different strength levels. It was found that consumer attitudes are an extremely strong factor that increases loyalty and improves satisfaction with mobile wallet applications in Thailand. We also found a very strong impact of satisfaction on loyalty with Thai consumers. This study helps to understand how specific factors influence consumer satisfaction with mobile wallet apps, and what drives consumers’ decisions to be loyal and satisfied customers.